2018
DOI: 10.1111/mec.14726
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genetic adaptation to a novel environment despite a genome‐wide reduction in genetic diversity

Abstract: Introduced species often colonize regions that have vastly different ecological and environmental conditions than those found in their native range. As such, species introductions can provide a deeper understanding into the process of adaptive evolution. In the 1880s, steelhead trout (Oncorhynchus mykiss) from California were introduced into Lake Michigan (Laurentian Great Lakes, North America) where they established naturally reproducing populations. In their native range, steelhead hatch in rivers, migrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 73 publications
1
76
0
Order By: Relevance
“…In sticklebacks, for instance, resident populations appear to be the result of independent colonization events (Defaveri, Shikano, Shimada, Goto, & Merilä, ). A reduction in genetic diversity is expected if these populations are the product of different founder effects as shown in steelhead trout (Willoughby, Harder, Tennessen, Scribner, & Christie, ). Under this scenario, local adaptation would be expected to play an important role in the differentiation between ecotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In sticklebacks, for instance, resident populations appear to be the result of independent colonization events (Defaveri, Shikano, Shimada, Goto, & Merilä, ). A reduction in genetic diversity is expected if these populations are the product of different founder effects as shown in steelhead trout (Willoughby, Harder, Tennessen, Scribner, & Christie, ). Under this scenario, local adaptation would be expected to play an important role in the differentiation between ecotypes.…”
Section: Discussionmentioning
confidence: 99%
“…As freshwater fish populations will probably be affected by climate change, one important aspect to bear in mind is the possibility of these animals adapting to ongoing climate warming. Adaptation to new environmental conditions in salmonids can be rapid, even in small populations with low genetic variation (Koskinen, Haugen, & Primmer, ; Willoughby, Harder, Tennessen, Scribner, & Christie, ), and physiological and genomic studies on salmonids support potential thermal adaptation (Chen, Farrell, Matala, Hoffman, & Narum, ; Chen, Farrell, Matala, & Narum, ; Narum et al., ). Many organisms, including salmonids, already show adaptive responses to climate‐driven changes such as elevated temperatures (Crozier & Hutchings, ; Jensen et al., ; Merilä & Hendry, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Willoughby et al. (in press) reported evidence of the blunting of local adaptions among steelhead from multiple Lake Michigan tributaries at a genome‐wide level after the stocking of non‐Michigan strains relative to the period before they were stocked. We found that regardless of the strain stocked or the receiving river, the straying proportion centered around 0.073.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches included the development of models to infer the effects of age and straying on catch rates and the development of growth models to determine the extent to which strain and sex influenced the ability to reach trophy size. We discuss straying results in terms of the potential deleterious effects of gene flow between stocked steelhead strays and self‐sustaining wild stocks, which may be adapting to local conditions (Waples ; Bartron and Scribner ; Willoughby et al., in press). By quantifying the degree to which each strain meets explicit strain‐specific fishery management objectives as well as how each strain supports steelhead management aims at the species level, fisheries managers can be more effective and efficient in the use of stocking as a tool to achieve desired outcomes.…”
mentioning
confidence: 99%